2017
DOI: 10.1186/s40885-017-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Systolic blood pressure but not electrocardiogram QRS duration is associated with heart rate variability (HRV): a cross-sectional study in rural Australian non-diabetics

Abstract: BackgroundA positive correlation between ECG derived QRS duration and heart rate variability (HRV) parameters had previously been reported in young healthy adults. We note this study used a narrow QRS duration range, and did not adjust for systolic blood pressure. Our aims are to investigate associations between systolic blood pressure (SBP), QRS duration and HRV in a rural aging population.MethodsA retrospective cross sectional population was obtained from the CSU Diabetes Screening Research Initiative data b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A limitation to our study is the use of an averaged 10 s, 12-lead ECG lead in order to obtain QRS duration. On the other hand, QRS duration from short ECG recordings has been previously used in large population studies [21,22]. We do not have data on medications that may have influenced QRS duration in this study.…”
Section: Discussionmentioning
confidence: 95%
“…A limitation to our study is the use of an averaged 10 s, 12-lead ECG lead in order to obtain QRS duration. On the other hand, QRS duration from short ECG recordings has been previously used in large population studies [21,22]. We do not have data on medications that may have influenced QRS duration in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Lee at al. [ 24 ] found that all HRV parameters were associated with the changes in systolic blood pressure. We did not find any correlation between blood pressure and HRV values for either the physical or the psychological stress tests—neither among resting nor delta values.…”
Section: Discussionmentioning
confidence: 99%
“…Mancia and Grassi [ 23 ] state that it is possible that the increased sympathetic drive interacts with blood pressure (BP). Lee et al [ 24 ] found that HRV indices were associated with an increase in systolic blood pressure. Systolic BP increases in a curvilinear manner as the load of treadmill running or cycling exercise increases; after the exercise, it takes 10–20 min to return to resting levels.…”
Section: Introductionmentioning
confidence: 99%